DETERMINAN PEMANFAATAN DUKUN BAYI DALAM PENDAMPING PROSES PERSALINAN DI DESA BULU CINA KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG - Rosa Veronika Sinaga, Lia; Asnawati Munthe, Seri; Zulfianda, Deva (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This research includes phenomenology research, namely research based on the symptoms that exist in the community with a focus on the determinants of the use of traditional birth attendants as birth attendants. Research is qualitative in that the results of research are not obtained through statistical procedures or other forms of calculation. Research informants were all mothers who had been assisted by traditional birth attendants. The method used is in-depth interviews with informants who are guided by research questionnaires. The results of this study indicate that childbirth assistance in Bulu China Village still utilizes the services of a traditional birth attendant. Based on the results of this study, it is suggested that the government intervene in determining the use of traditional birth attendants by providing training so that health workers can empower dukuns to carry out health services so that they increase the level of public health.